Matters of participation: notes on the study of dignity and learning. (1st October 2020) - Espinoza, Manuel Luis; Vossoughi, Shirin; Rose, Mike; Poza, Luis E.
ABSTRACT: Meaningful participation (i.e., substantive involvement in socially vital activities) and educational dignity (i.e., the multifaceted sense of a person's value generated via substantive intra- and inter-personal learning experiences that recognize and cultivate one's mind, humanity, and potential) are vital and interrelated social phenomena. Conceptually, the two are salient for research related to learning and educational rights. Accordant with a cultural-historical framework, we have adopted and modified a social interactional methodological approach that allows us to set forth indicia of meaningful participation and educational dignity. To achieve these ends, we examine two information sources: 1) audio recordings of a 1962 voter registration workshop in the Southern United States; and 2) audio-video recordings of a college preparatory program for high school-age migrant students in California during the early 2000s called the Migrant Student Leadership Institute. Close examination of interactions in both spaces reveals the moment-to-moment unfolding of meaningful participation and educational dignity.